Decentering nationalism: Representing and contesting Chimurenga in Zimbabwean popular culture - Mawere, Tinashe (University of the Western Cape, 2016)
Philosophiae Doctor - PhD === This study seeks to uncover the non-coercive, intricate and insidious ways which have generated both the 'willing' acceptance of and resistance to the rule of Robert Mugabe and ZANU-PF in Zimbabwe. I consider how popular culture is a site that produces complex and persuasive meanings and enactments of citizenship and belonging in contemporary Zimbabwe and focus on 'agency,' 'subversion' and their interconnectedness or blurring. The study argues that understanding nationalism's impact in Zimbabwe necessitates an analysis of the complex ways in which dominant articulations of nationalism are both imbibed and contested, with its contestation often demonstrating the tremendous power of covert forms of resistance. The focus on the politics of popular culture in Zimbabwe called for eclectic and critical engagements with different social constructionist traditions, including postcolonial feminism, aspects of the work of Louis Althusser and Michel Foucault. My eclectic borrowing is aimed at enlisting theory to analyse ways in which co-optation, subversion and compromise often coexist in the meanings generated by various popular and public culture forms. These include revered national figures and symbols, sacrosanct dead bodies and retrievals, slogans and campaign material, sport, public speeches, the mass media and music. The study therefore explores political sites and responses that existing disciplinary studies, especially politics and history, tend to side-line. A central thesis of the study is that Zimbabwe, in dominant articulations of the nation, is often constituted in a discourse of anti-colonial war, and its present and future are imagined as a defence of what has already been gained from previous wars in the form of "chimurenga." I argue that formal sites of political contestation often reinforce forms of patriarchal, heterosexist, ethnic, neo-imperial and class authoritarianism often associated only with the ZANU PF as the overtly autocratic ruling party. In turning to diverse forms of popular culture and their reception, I identify and analyze sites and texts that, rather than constituting mere entertainment or reflecting organized and party political struggles, testify to the complexity and intensity of current forms of domination and resistance in the country. Contrary to the view that Zimbabwe has been witnessing a steady paralysis of popular protest, the study argues that slogans, satire, jokes, metaphor, music and general performance arts by the ordinary people are spaces on which "even the highly spectacular deployment of gender and sexuality to naturalize a nationalism informed by the 'efficacy' of a phallocentric power 'cult' is full of contestations and ruptures."